Serological Relationships in the Leptodactylus pachypus Species Group (Amphibia, Salientia) - Cei, José Miguel Alfredo María (1965)
Precipitin tests indicate that Leptodactylus ocellatus and L. chaquensis are more closely related than either is to L. pentadactylus. However, the serological differences between L. ocellatus and L. chaquensis support a separate specific ranking for these forms. Populational variations of the specific antigens occur in all 3 species.